A College Athlete's Return from Severe Aplastic Anemia - Cole Miller; Alex Walker (Bowling Green State University, 2019)
Please enjoy Volume 5, Issue 1 of the JSMAHS. In this issue you will find Professional and under graduate research abstracts, case reports, and critically appraised topics. Thank you for viewing this 5th Annual OATA Special Edition.